Food Security Mapping in Padang City Using Geographical Information Systems (Case Study: Beef) - Oktavia, Nurike; Helmi, Adlina Safitri; Ahmad, Nofan Hadi; Ramadhani, Indah Kurnia; Triha, Hadigufri (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
In Indonesia, the cattle agricultural business is one of the most significant food commodities for comply nutritional needs. The variable availability of cattle supplies is a challenge that the Padang City Agriculture Service must tackle. As a result, to establish the state of food security in Padang City, food security indicators must be calculated and analyzed. Food Security Quotient (FSQ) approach was used in this study to map the logistical network and beef food security. Following that, an information system based on a Geographic Information System (GIS) was created to represent the flow of the beef supply chain in Padang City. It was discovered from direct observations beef supply chain network in Padang City comprises of a fresh beef and a frozen beef supply chain. Beef suppliers from other regions, local breeders, feed lotters, slaughterhouses, wholesalers, retail traders, hotel / supermarket /restaurant/ catering consumers, rendang processing industry consumers (MSMEs), home consumers small-scale dining, and household consumers are all involved in the fresh beef supply chain. The analysis of the level of food security in Padang City revealed that three sub-districts were in the secure state, three were in a moderate state, and five were in a vulnerable state. The developed GIS is supposed to aid decision making in Padang City on food security predictions.